Anarchism, Geohistory, and the Annales: Rethinking Elisée Reclus's Influence on Lucien Febvre. (April 2015) - Ferretti, Federico
It has been hypothesized that the celebrated geographer and anarchist Elisée Reclus was a decisive influence on several concepts that are characteristic of the Annales School, the historical French school of the Annales d'histoire économique et sociale, such as longue durée, material history, space-movement, and geohistory. Yet no systematic research exists on the topic. In this paper, on the basis of textual analysis and new archival materials recently published in France, I argue that Reclus's influence particularly affected the Annales's founder Lucien Febvre, and that it springs from not only Febvre's scholarly interest in Reclus, but also his early engagement in socialist milieus and sympathies for both anarchism and figures like Pierre-Joseph Proudhon. Finally, I show how these topics could be useful for present debates on critical social theory and radical geographies.